ANALISIS MANAJEMEN RISIKO KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Retno Santi Nur Azizah; Aqilah Az Zahra; Dian Hakip Nurdiansyah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to determine the company's financial risk management at PT. Trisula Textile Industries. Many business risks of multinational companies have been identified, and many of the risks experienced have also been overcome. However, there has never been an in-depth study on all types of business risks that may occur, and how to best respond to these risks. Risk management is an important part of the management strategy of all companies. The process by which an organization with the right method is able to show the risks that occur in one activity that lead to success in each activity of all activities. The focus of risk management is the identification and how to overcome a risk. Maximizing company value Every company has an interest in measuring its performance. The company's ability to generate profits is the main focus in assessing the company's performance, because profit is not only a measure of the company's ability to achieve its goals. Investor liability is also an element of the company's value creation, which shows the company's future prospects. Firm value is influenced by the level of debt policy (leverage). Of course, the debt policy implemented by the company contains risks, and the company will face a fixed burden, of course, these expenses include costs. The research methodology used for this writing is a qualitative descriptive analysis technique. Data collection techniques using literature study. The object of this research is to know the financial risk management on the company's financial performance at PT. Trisula Textile Industries period 2020. Keyword: Risk Management, Financial Ratios, Altman Z-Score